2020
DOI: 10.1111/1440-1681.13264
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐876‐5p represses the cell proliferation and invasion of colorectal cancer through suppressing YAP signalling via targeting RASAL2

Abstract: Aberrant expression of microRNA‐876‐5p (miR‐876‐5p) is implicated in the progression of multiple human cancers. However, the potential role of miR‐876‐5p in colorectal cancer remains poorly understood. The purpose of the current study was to investigate the potential role of miR‐876‐5p in colorectal cancer. miR‐876‐5p expression was significantly downregulated in colorectal cancer tissues and cell lines compared with normal controls. Gain‐of‐function assays revealed that miR‐876‐5p overexpression effectively r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…YAP1 signaling plays a key role in the progression of colorectal cancer 28,33–36 . Nuclear levels of YAP1 are frequently up‐regulated in colorectal cancer, and the expression of YAP1 target genes, such as CTGF and CRY61, is also increased 23,37,38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YAP1 signaling plays a key role in the progression of colorectal cancer 28,33–36 . Nuclear levels of YAP1 are frequently up‐regulated in colorectal cancer, and the expression of YAP1 target genes, such as CTGF and CRY61, is also increased 23,37,38 .…”
Section: Discussionmentioning
confidence: 99%
“…The luciferase reporter assay of YAP1 was performed in accordance with a previously described method 28 …”
Section: Methodsmentioning
confidence: 99%
“…MiR-487a-3p serves as a tumor suppressor in prostate cancer by targeting CCND1 (cyclin D1, CCND1) [ 33 ]. MiR-876-5p has been validate as a tumor suppressor in multiple tumors including breast cancer, gastric cancer, colorectal cancer, head and neck squamous cell carcinoma, liver cancer and so on [ 16 , 17 , 34 36 ], and its downstream targets includes TFAP2A, MITF, RASAL2, vimentin, DNMT3A and so on [ 16 , 17 , 34 36 ]. In this study, for the first time, we found that miR-876-5p was remarkably down-regulated in PCa tissues and cells, and could inhibit the proliferation of PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that RASAL2 exerts tumor‐promoting behavior by enhancing the activation of the oncogenic protein YAP1 14,29 . Inhibition of RASAL2 up‐regulated the phosphorylation of YAP1, and increased translocation of YAP1 from the nucleus to cytoplasm, leading YAP1 inactivation in colorectal cancer cells 14 .…”
Section: Discussionmentioning
confidence: 99%